Retinol dehydrogenase 12 (RDH12): Role in vision, retinal disease and future perspectives. (November 2019) - Sarkar, Hajrah; Moosajee, Mariya
Abstract: Retinol dehydrogenase 12 (RDH12) is an NADPH-dependent retinal reductase, which is expressed in the inner segments of the photoreceptors. It functions as part of the visual cycle, which is a series of enzymatic reactions required for the regeneration of the visual pigment, and has also been implicated in detoxification of lipid peroxidation products. Mutations in RDH12 have been linked to Leber congenital amaurosis (LCA) and autosomal dominant retinitis pigmentosa. A number of in-vitro studies have shown that mutations in RDH12 result in little or no enzyme activity. Knockout mouse models however do not recapitulate the severe phenotype observed in patients, resulting in a limited understanding of the disease mechanisms. With gene replacement and small molecule drugs emerging for inherited retinal dystrophies, herein we provide a review of RDH12 structure, its role in vision and the current understanding of disease mechanisms linked to clinical phenotype to support therapeutic development. Highlights: Retinol dehydrogenase 12 (RDH12) structure, function and role in vision. Disease mechanisms and clinical phenotype of RDH12 retinopathies. Therapeutic avenues and consideration for future research.